The Interrelatedness of Gender-Stereotypical Interest Profiles and Students’ Gender-Role Orientation, Gender, and Reasoning Abilities - Ehrtmann, Lisa; Wolter, Ilka; Hannover, Bettina (Frontiers in Psychology, 2019)
This study investigates early secondary school students’ gender-stereotypical interest profiles and how they relate to students’ gender-role orientation, i.e., their traditional or egalitarian attitudes towards gender roles. Gender-stereotypical interest profiles are described by relatively high interests in either female or male-stereotypical domains and low interests in domains that are not associated to the own gender group. In a study conducted with 4457 students (49.2% female, sixth-graders) with data from the German National Educational Panel Study*, four interest profiles were derived from the combined latent class analysis of two academic interest domains (mathematics and German) and six vocational interest domains (realistic, investigative, artistic, social, enterprising, and conventional). Aside from two gender-stereotypical interest profiles, two gender-undifferentiated interest profiles were found. One undifferentiated interest profile was marked by generally high interests in all domains, the other by generally low interests in all domains. Students in the male-stereotypical interest profile had high values in the mathematics, realistic, investigative, and enterprising domains and low interest in the German, artistic, social, and conventional domains. The female-stereotypical interest profile was marked by the opposite pattern. The results further showed that students more likely belonged to the high or female interest profiles when they expressed egalitarian gender-role orientations. Also, boys were more likely members of the female interest profile than were girls of the male interest profile. Students with low reasoning skills were generally more likely members of the low interest profile group. Results are discussed with respect to the question whether interest profiles are more predictive of students’ academic development than single domain-specific measures of interest.